Let's look at each student's work step by step to see who's correct.
Jamal's Work:
- He started with the equation x² + 4x - 12 = 0.
- He factored it as (x + 6)(x - 2) = 0.
- He set both factors equal to zero: x + 6 = 0 and x - 2 = 0.
- Solving these gives x = -6 and x = 2.
George's Work:
- He started with the equation x² + 4x - 5 = 7.
- Before factoring, he needs to move the 7 to the other side to set it to zero, so it should be x² + 4x - 12 = 0.
- He factored it as (x + 5)(x - 1) = 7, which is incorrect because you can't factor an equation that's still equal to 7.
- Then he set the factors equal to zero: x + 5 = 0 and x - 1 = 0, leading to solutions of x = -5 and x = 1.
Analysis:
-
Jamal's Solution: He set the equation correctly to zero and factored it correctly. Therefore, his use of the Zero Product Property is correct because both factors equaled zero when set.
-
George's Solution: He did not set the equation equal to zero before factoring; he kept it equal to 7. Therefore, his factoring is incorrect, and this means he cannot use the Zero Product Property properly.
In simple words, Jamal did everything right and got the right answer because he followed all the steps correctly. George, however, made a mistake in his first step by not setting the equation to zero before trying to factor it, which caused his entire solution to be wrong.